2019
DOI: 10.7759/cureus.6342
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role of Elevated CA 19-9 Levels in the Evaluation of Clinical Characteristics of Mature Cystic Ovarian Teratomas? A Systematic Review and Meta-analysis

Abstract: The role of preoperative CA 19-9 levels in patients with ovarian mature cystic teratoma (MCT) and the association of elevated levels of the biomarker with patients' and tumor characteristics were evaluated. Four electronic databases were searched for articles published up to September 2019. Trials that evaluated the significance of elevated CA 19-9 in patients with ovarian MCTs and publications with > 20 patients were considered eligible for inclusion. Seven studies that included 995 patients with an ovarian M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…Particularly in premenopausal women where preserving fertility is crucial, the higher preoperative diagnostic accuracy of adnexal masses is needed. Preoperative CA 19-9 has potential diagnostic utility, if supplementary to imaging[ 120 ] and other tumor markers. In a study by Cho et al [ 121 ] involving 322 patients, OMCTs were associated with isolated elevation of CA 19-9, whereas cancers were associated more with a simultaneous elevation of CA 19-9 and CA 125[ 121 ].…”
Section: Future Uses Of Ca 19-9mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in premenopausal women where preserving fertility is crucial, the higher preoperative diagnostic accuracy of adnexal masses is needed. Preoperative CA 19-9 has potential diagnostic utility, if supplementary to imaging[ 120 ] and other tumor markers. In a study by Cho et al [ 121 ] involving 322 patients, OMCTs were associated with isolated elevation of CA 19-9, whereas cancers were associated more with a simultaneous elevation of CA 19-9 and CA 125[ 121 ].…”
Section: Future Uses Of Ca 19-9mentioning
confidence: 99%
“…Elevated CA 19-9 can also predict complications and guide management. A meta-analysis by Prodromidou et al [ 120 ] involving 995 patients in nine studies demonstrated a correlation between elevated CA 19-9 levels and significantly larger mean size of OMCT and ovarian torsion[ 120 ]. These studies, however, did not screen for concomitant conditions causing raised CA 19-9.…”
Section: Future Uses Of Ca 19-9mentioning
confidence: 99%
“…Herein, we report the level of CA 19–9 can be extremely increased in the case of benign ovarian teratoma without any complications. CA 19–9, also known as cancer antigen 19–9, is a tetrasaccharide carbohydrate that has been suggested as a prognostic tumor marker in patients with pancreatic cancer [ 7 ]. Besides malignancies, CA 19-9 levels may also increase in benign pancreatobiliary, hepatic, and pulmonary diseases; thyroiditis; diabetes mellitus; autoimmune diseases; and gynecologic diseases such as endometriosis and mucinous ovarian tumors [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…CA 19–9, also known as cancer antigen 19–9, is a tetrasaccharide carbohydrate that has been suggested as a prognostic tumor marker in patients with pancreatic cancer [ 7 ]. Besides malignancies, CA 19-9 levels may also increase in benign pancreatobiliary, hepatic, and pulmonary diseases; thyroiditis; diabetes mellitus; autoimmune diseases; and gynecologic diseases such as endometriosis and mucinous ovarian tumors [ 7 , 8 ]. The increase in CA 19-9 levels in benign diseases can be explained by inflammation and proliferation of non-tumorous tissue or metabolic malfunction [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, one study reported correlation between tumour diameter and bilaterality and the highest CA19-9 level of 25 590 U/mL in a case 17 . In dermoid cysts, elevated CA19-9 levels may be caused by rupture and leakage from the cyst wall into the blood stream or a weakened cyst wall in a larger diameter cyst 18 , may be related to torsion of the ovary and to the extent of the necrosis 14 , and may be an indicator for early surgical intervention owing to higher risks of torsion and larger cyst size 19 .…”
Section: Discussionmentioning
confidence: 99%